Active Fuelling of a Passenger Car Sized Pre-Chamber Ignition System with Gaseous Components of Gasoline - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2020)
Homogeneous lean or diluted combustion can significantly increase the efficiency of spark ignition engines. Active fuelled pre-chamber ignition systems can overcome the problem that common spark ignitions systems are incapable to ignite strongly diluted mixtures. A small portion of the charge is burned in a separated chamber, which is connected to the main chamber by multiple small orifices. The combustion inside the pre-chamber generates hot gases, which penetrate into the main chamber and ignite the diluted charge on multiple sites. Active pre-chamber ignition systems feature a separate fuelling or scavenging system in addition to the one of the main combustion chambers. Preferably, gaseous fuel is used for the pre-chamber fuelling allowing better dosing accuracy and mixture preparation inside the pre-chamber. Using the mixture of air and gasoline vapour present in the fuel tank above the liquid level for fuelling the pre-chamber is one key element enabling an active pre-chamber ignition system for passenger cars. An experimental setup was built to simulate a fuel tank under different environmental conditions. The composition of the gasoline vapour-Air-mixture inside the tank was analyzed for various industry known reference fuels under extreme conditions. The necessary concentration of hydrocarbons was accomplished with all tested fuels. Additionally, the system was integrated into a engine testbench to analyze the engine combustion depending on the pre-chamber fuelling. The dosing of gasoline vapour-Air-mixture into the pre-chamber is implemented via a solenoid valve together with a self-developed check valve. Investigations in the especially critical low-load range show stable engine combustion in all conditions if the dosed mass of the fuel vapor-Air-mixture is adapted to the concentration of hydrocarbons present in this mixture.
Created from Fastlane, Scopus look-up